Google Classroom: The Web-Based Media for Teaching English - Widi Andewi; Dwi Pujiastuti (Jurnal Penelitian Ilmu Pendidikan, 2021)
This study investigates whether: 1) Google Classroom is more effective than the conventional method for teaching writing; 2) The high creativity students have better writing skills than those who have low creativity, and; 3) Interaction between teaching method and students' creativity in teaching writing occurs. This quasi-experimental study was conducted at STMIK Pringsewu in the academic year of 2020/2021.  The sample of this research was two classes, the namely experimental class taught using Google Classroom, and the control class taught using a conventional method. Each class consisted of 20 students, so the total sample is 40 students. The sample was obtained by using the cluster random sampling technique. Each class was divided into two groups, consisting of ten high creativity students and ten low creativity students. The data of this research were obtained from a writing test to find out students' writing scores. Then, the data were analyzed by using 2x2 multifactor analysis of variance ANOVA and Tukey test. The results show that the mean scores of A1B1 are 82.40, A2B1 is 75.30, A1B2 is 68.70, and A2B2 is 69.70. This study implies that Google Classroom is an effective method in teaching writing and is suitable to be implemented to those having high creativity. Google Classroom: Media Berbasis Web untuk Mengajar Bahasa Inggris Penelitian ini menyelidiki apakah: 1) Google Classroom lebih efektif daripada metode konvensional dalam mengajar menulis; 2) Siswa yang kreativitasnya tinggi memiliki kemampuan menulis yang lebih baik dibandingkan siswa yang kreativitasnya rendah; dan 3) Terjadi interaksi antara metode pengajaran dan kreativitas siswa dalam pembelajaran menulis. Penelitian kuasi eksperimen ini dilakukan di STMIK Pringsewu pada tahun pelajaran 2020/2021. Sampel penelitian ini memiliki dua kelas yaitu kelas eksperimen yang diajar menggunakan Google Classroom dan kelas kontrol yang diajar dengan metode konvensional. Setiap kelas terdiri dari 20 siswa, sehingga jumlah sampel adalah 40 siswa. Sampel diperoleh dengan menggunakan teknik cluster random sampling. Setiap kelas dibagi menjadi dua kelompok yang masing-masing terdiri dari 10 siswa kreativitas tinggi dan 10 siswa kreativitas rendah. Data penelitian ini diperoleh dari tes menulis untuk mengetahui nilai menulis siswa. Kemudian data dianalisis dengan menggunakan analisis multifaktor varians 2x2 dan uji Tukey. Hasil penelitian menunjukkan bahwa nilai rata-rata A1B1 adalah 82,40, A2B1 adalah 75,30, A1B2 adalah 68,70, dan A2B2 adalah 69,70. Hasil penelitian ini mengimplikasikan bahwa Google Classroom merupakan metode yang efektif dalam pengajaran menulis dan cocok untuk diterapkan bagi mereka yang memiliki kreativitas tinggi.